2008
DOI: 10.1021/ef800284t
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Contaminant Transport in Underground Coal Gasification

Abstract: In order to study and discuss the impact of contaminants produced from underground coal gasification on groundwater, a coupled seepage-thermodynamics-transport model for underground gasification was developed on the basis of mass and energy conservation and pollutant-transport mechanisms, the mathematical model was solved by the upstream weighted multisell balance method, and the model was calibrated and verified against the experimental site data. The experiment showed that because of the effects of temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The UCG has been performed in over 75 trials throughout the world, and despite most of the UCG trials not experiencing significant environmental issues, potential pollution is the biggest public and regulatory concern [17]. Several researchers who focused on the generation and transport of contaminants via experimental and numerical analyses [18][19][20][21][22][23][24][25] have suggested that operating the UCG process above the hydrostatic pressure can pose an environmental concern due to the chemical reactions in the groundwater environment depending on mineral composition, temperature, concentration of syngas components and the chemical composition of groundwater. However, modelling of contaminant transport and reactions received less attention as it is a complex process with multiple aspects involving heat, mass, stress-strain and physico-chemical reactions [18,26].…”
Section: Fig 1 Schematic Diagram Of the Overall Ucg Processmentioning
confidence: 99%
“…The UCG has been performed in over 75 trials throughout the world, and despite most of the UCG trials not experiencing significant environmental issues, potential pollution is the biggest public and regulatory concern [17]. Several researchers who focused on the generation and transport of contaminants via experimental and numerical analyses [18][19][20][21][22][23][24][25] have suggested that operating the UCG process above the hydrostatic pressure can pose an environmental concern due to the chemical reactions in the groundwater environment depending on mineral composition, temperature, concentration of syngas components and the chemical composition of groundwater. However, modelling of contaminant transport and reactions received less attention as it is a complex process with multiple aspects involving heat, mass, stress-strain and physico-chemical reactions [18,26].…”
Section: Fig 1 Schematic Diagram Of the Overall Ucg Processmentioning
confidence: 99%
“…These effluents, if not treated appropriately, can pose a serious environmental risk to surface waters. Experimental simulations and field studies on the formation and migration of contaminants around the UCG test sites identified a broad range of hazardous species (Kapusta and Stańczyk 2011;Edgar et al 1981;Walters and Niemczyk 1984;DeGraeve et al 1980;Shackley et al 2006;Stuermer et al 1982;Yang 2009;Smoliński et al 2013). The major organic groundwater pollutants are typically phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The major organic groundwater pollutants typical of UCG are phenols, benzene and its derivatives (BTEX), polycyclic aromatic compounds (PAHs) and certain heterocyclic compounds containing nitrogen, sulphur and oxygen heteroatoms. The inorganic matrix includes ionic compounds, such as ammonia, cyanides, sulphates, chlorides and wide range of metal and metalloid elements (Stuermer et al, 1982;Edgar et al, 1981;DeGraeve et al, 1980;Yang, 2009;Kapusta and Stańczyk, 2011;Liu et al, 2006aLiu et al, , 2006b.…”
Section: Introductionmentioning
confidence: 99%